Citrus reticulata flavonoids as a valuable source for reducing meat-borne Aeromonas hydrophila - Khairy Elbarbary, Nady; Al-Qaaneh, Ayman M.; M. Bekhit, Mounir; Abdelhaseib, Maha; A. Gomaa, Reda; Ali, Marwa A.; Salem, Mohamed M.; M.L. Malak, Nermeen (Italian Journal of Food Science, 2024)
Meat products are one of the nutritious diet options available to consumers. However, meat products have the potential to serve as a reservoir of food-borne infections, such as those caused by Aeromonas species, which pose a significant risk to public health. A total of 270 samples, 30 of each minced beef, meatball, beef burger, chicken nuggets, chicken pane, chicken burger, canned anchovy, canned mackerel, and canned sardine, were obtained from supermarkets in Aswan Province, Egypt, to analyze the occurrence and virulence features of Aeromonas hydrophila. Influence of Citrus reticulata peel extract on the A. hydrophila count and its virulence capacity after different marinating periods was also analyzed. The obtained results revealed that the Aeromonas counts ranged from 2.02±0.30 to 4.21±0.27 log10 CFU/g and 37% of the analyzed samples were contaminated with Aeromonas spp. The main strains discovered were A. hydrophila (13.3%), A. sobria (9.6%), A. caviae (7.4%), A. veronii (4%), and A. fluvialis (2.6%). It was found by polymerase chain reaction that all tested strains (n = 36) belonged to Aeromonas spp., and 89% were identified as A. hydrophila. In contrast, virulence genes aerolysin (aerA) and cytotoxic enterotoxin (act) were found in 61.1% and 50% of the tested isolates, respectively, with a wide range of antibacterial resistance. Additionally, the influence of Citrus reticulata peel extract on A. hydrophila counts at different marinating periods declined significantly with increased concentration without major changes in the sensory criteria.